“You Can’t Meet Everyone's Needs After-Hours”: After-Hours Domestic and Family Violence Services in Rural and Remote Areas - Hanley, Natalia (Violence against women, 2023)
Domestic and family violence is a significant issue in the Murrumbidgee region of New South Wales, Australia, mirroring national and international concerns about gender-based violence. Generally, there are known barriers associated with providing domestic and family violence (DFV) services in rural and remote communities; however, little research has considered the specific service needs and service barriers in the after-hours period. This is crucial. The already limited rural and remote services available during business hours are further constricted in the after-hours period. This article reports on research about after-hours service need and service challenges in six target communities in the Murrumbidgee region.